Fatigue limit investigation of 6061-T6 aluminum alloy in giga-cycle regime - Takahashi, Yoshimasa; Yoshitake, Hiroaki; Nakamichi, Ryota; Wada, Takuya; Takuma, Masanori; Shikama, Takahiro; Noguchi, Hiroshi (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2014)
In order to investigate the fatigue limit micro-mechanism of a precipitation-hardened Al–Mg–Si alloy (6061-T6), the alloy was subjected to very-high-cycle fatigue (VHCF) of over 109 cycles by an ultrasonic fatigue method. Two kinds of specimens, one with smooth surface and the other with a small artificial hole on the surface, were compared. The smooth specimens showed no distinct fatigue limit. Conversely, the holed specimens showed clear fatigue limit which had been generally deemed to be absent in non-ferrous alloys. In addition to the conventional fatigue crack growth (FCG) observation by replica technique, metallographically critical analyses by electron backscattered diffraction (EBSD) and cross-sectional focused ion beam (FIB) were conducted to reveal the micro-plasticity associated with FCG. It was found that the fatigue life of smooth specimens at low stress amplitude was controlled by an unstoppable FCG mechanism mediated by persistent slip bands (PSBs). On the other hand, the emergence of distinct fatigue limit in holed specimens was attributed to a non-propagating crack having mode I characteristics in essence. No coaxing effect was, however, confirmed for such non-propagating cracks. The above results, which were somewhat different from previous ones obtained by rotating bending under normal frequency, were discussed in terms of both metallurgical and mechanical points of view.